2008
DOI: 10.3758/pbr.15.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Feature integration without visual attention: Evidence from the correlated flankers task

Abstract: It is widely assumed that the separable features of visual objects, such as their colors and shapes, require attention to be integrated. However, the evidence in favor of this claim comes from experiments in which the colors and shapes of objects would have to be integrated and then also subjected to an arbitrary, instruction-based, stimulus-response (S-R) translation in order to have an observable effect. This raises the possibility that attention is not required for feature integration, per se, but is only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Furthermore, it has recently been shown that these frequency-or contingency-based effects can be rooted in color/shape conjunctions, even when participants are instructed to ignore these particular items (Mordkoff & Halterman, 2008). Therefore, the design used by Feintuch and Cohen (2002), with frequency ratios of three-and six-to-one, is potentially biased against the between-object, redundant-targets condition, since this was the only condition under which a rapid shift of attention away from the non-target item -and, presumably, therefore, towards the item containing the target feature(s) -would never occur.…”
Section: Objects Vs Dimensions Revisitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has recently been shown that these frequency-or contingency-based effects can be rooted in color/shape conjunctions, even when participants are instructed to ignore these particular items (Mordkoff & Halterman, 2008). Therefore, the design used by Feintuch and Cohen (2002), with frequency ratios of three-and six-to-one, is potentially biased against the between-object, redundant-targets condition, since this was the only condition under which a rapid shift of attention away from the non-target item -and, presumably, therefore, towards the item containing the target feature(s) -would never occur.…”
Section: Objects Vs Dimensions Revisitedmentioning
confidence: 99%
“…(It's important to note that the potential for the sort of bias that was included in their design was not known at the time; it was first discussed in Mordkoff & Halterman, 2008, which appeared several years later.) In brief, when both target features were parts of one item, only one possible combination of color and shape ever appeared in the opposite location.…”
Section: Objects Vs Dimensions Revisitedmentioning
confidence: 99%
“…2 Within the context of the present report, then, high contingency trials are those in which an item of a category is presented in the color in which most of the other items of that category are presented (e.g., "lawyer" in grey), whereas low contingency trials are those in which the item is presented in another colour (e.g., "doctor" in orange). If colour-word 1 This is also generally true of related learning paradigms, such as the flanker contingency paradigm (Carlson & Flowers, 1996;Miller, 1987;Mordkoff, 1996;Mordkoff & Halterman, 2008), where flanking letters are predictive of a central target letter, and other related paradigms (e.g., Musen & Squire, 1993). 2 Because the high contingency category for each colour was fully counterbalanced across participants (e.g., professions most often in blue for 1/3 of the participants, most often in orange for another 1/3, and most often in grey for the remaining 1/3), all word-colour pairs served equally often as both high and low contingency trials (across participants).…”
Section: Introductionmentioning
confidence: 99%
“…In the study of contingency learning, one useful and highly robust tool is the colour word contingency learning paradigm (Schmidt & Besner, 2008;Schmidt, Crump, Cheesman, & Besner, 2007;Schmidt & De Houwer, 2016a; for related paradigms, see Carlson & Flowers, 1996;Levin & Tzelgov, 2016;Miller, 1987;Mordkoff & Halterman, 2008;Schmidt & De Houwer, 2012b, 2012c. In the typical preparation, participants are presented with coloured neutral words (e.g., "plate" in green) and their task is to identify the print colour while ignoring the word.…”
Section: Introductionmentioning
confidence: 99%